Framing Drug Use - Fitzgerald, J. author. aut Link
XII, 289 p.
Keywords: This book examines the forces that shape psychoactive drug use. The approach, informed by poststructuralist semiotics, culture, phenomenology and contemporary theories of affect, illuminates the connections between drugs, bodies, space, economy and crime.